A práxis político-educativa dos trabalhadores da construção civil - Furtado, Daniel Bezerra (2018)
This is an investigation of a theoretical nature about the praxis developed by the instances of the labor movement through the Marxian theoretical contribution. In the bibliographical research on the works of Marx and Engels and contributions of their interpreters, such as Vázquez, Sousa Júnior and Kosik, we intend to analyze the political-educational praxis category as fundamental for the understanding of Marxist theory and how the understanding of its meaning can contribute to the educational and self-educative process of the proletariat. We will analyze their relationship with work and education as the basis of the Marxist program for education. Then, based on the writings of Lenin, Rosa Luxemburg, Trotsky, and Gramsci, we will analyze the performance of parties, trade unions, intellectuals and other class entities as mediators of revolutionary praxis. Next, we will investigate the political-syndical and educational initiatives carried out at the Union of Workers in the Civil Construction Industry of the Metropolitan Region of Fortaleza, starting with the constitution of the trade union opposition in 1988, passing through its election and tenure as a leading group. Its political-syndical activity is responsible for establishing, building and consolidating a political-educational praxis aimed at raising the level of awareness of construction workers. Finally, we will focus on the educational experiences that are not institutionalized: the literacy project promoted by the union, the employers' school and the School of the Peon, for the literacy of workers. In this direction, we will reflect on the possibilities of developing a transformative praxis and a permanent and dialectical process between the educational activity of the teachers, from school spaces that were not raised by the State and consequently collide with it, as a counterpoint, rowing against with the prospect of educating workers, who, in developing an active political and labor union in the class field, feel the need to become literate and educate themselves, in order to better understand the world they live in and to form themselves politically in search of their emancipation.